„Trotz mancher Schwierigkeiten“: zu den Auslandsreisen deutscher Geisteswissenschaftler zwischen 1933 und 1945 - Albrecht, Andrea; Klausnitzer, Ralf (Berichte zur Wissenschaftsgeschichte, 2020)
In the years of National Socialism, and even during World War II, German scientists traveled abroad extensively. While international travels by natural scientists were studied in some detail, travels by scholars in the humanities have been studied to a much lesser degree, even though travel documents offer valuable insights into the regulated internationality of National Socialism. - We provide a first overview of international travels of scholars in the humanities between 1933 and 1945. The examples demonstrate how travelling academics dealt with conflicting expectations, justified their intentions, articulated disappointment, offered pragmatic advice for the further shaping of contacts abroad, and in this way became active participants of the resource ensemble of academia and politics. The study is based on extensive material from the political archive of the Auswärtiges Amt and the archive of the Reichsministerium für Wissenschaft, Erziehung und Volksbildung from the Bundesarchiv which to this date have been hardly explored.